Research on Internet Use and Dissemination of Chinese Public Welfare Organizations - Pan, Lin; Xie, Dong (Archives of Business Research, 2018)
According to the fifth survey about the situation of internet technology and diffusion ability in 531 public welfare organizations in China, the digital media application gap assuredly exists between Chinese public welfare organizations. There are small gaps in the use and dissemination of the internet, including industry information sharing, agencies publicity, public welfare concepts advocating and public credibility improving. The gap exists in the internet application of public welfare organizations, including the access to internet resources, knowledge and information management, data online analysis, and internet collaboration. At the age of the internet, the development situation of public welfare organizations will depend on whether the public welfare organization can actively catch the opportunity and challenge of internet technology to get the digital application ability. The reduction of internet technology will assuredly improve communication strategy of public welfare organization.